2010
DOI: 10.1111/j.1526-100x.2010.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Succession as a Restoration Tool for Maritime Cliff‐top Vegetation in Brittany, France

Abstract: The impacts of human activities, especially those caused by tourism, have resulted in the destruction of coastal cliff-top heathland and grassland vegetation. The loss of these natural habitats has led land managers to reduce human pressure and its impacts on the vegetation cover. Access has been restricted to stop the destruction, and restoration techniques are mainly based on the natural resilience of the vegetation. There have been few scientific reviews of the success of existing restoration operations thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Similarly, in Argentina, Cuevas & Zalba (2010) found that invasive pine removal allowed grassland recovery within four years if removal occurred early in the invasion process. By fencing to remove grazers, Sawtschuk et al (2010) found that maritime clifftop vegetation recovered within 16 years. Interestingly, the few sites that did not recover in this time frame were ones invaded by an exotic species.…”
Section: Restoration To Guide Recoverymentioning
confidence: 98%
“…Similarly, in Argentina, Cuevas & Zalba (2010) found that invasive pine removal allowed grassland recovery within four years if removal occurred early in the invasion process. By fencing to remove grazers, Sawtschuk et al (2010) found that maritime clifftop vegetation recovered within 16 years. Interestingly, the few sites that did not recover in this time frame were ones invaded by an exotic species.…”
Section: Restoration To Guide Recoverymentioning
confidence: 98%
“…Long‐term surveys conducted on passive restoration projects have shown that typical clifftop vegetation is able to spontaneously recolonize bare soil following vegetation degradation as long as the soil has not been too damaged (Sawtschuk et al ). However, the effectiveness of this method after heavy degradation, such as building deconstruction or high human trampling pressure, has not been assessed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these experiments have been published in specialized scientific journals (Rozé 1995;Bioret & Géhu 2008;Gallet et al 2010;Sawtschuk et al 2010Sawtschuk et al , 2012 as well as in managers' handbooks for the nonscientist stakeholders (Enoul 1999;Bioret & Gallet 2015). Numerous articles have also been published in nonindexed journals (Bioret & Rivière 2004;Gallet et al 2009Gallet et al , 2011Sawtschuk et al 2015).…”
Section: Evolution Of Assessment and Monitoring Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past long‐term ecological surveys represent an efficient way to elaborate vegetation trajectory models and build up hypotheses on potential dynamics that could occur in newly restored sites or in on‐going restoration or conservation projects (Sawtschuk et al. ). Based on these surveys, vegetation classification and multivariate analyses allow description of vegetation states, and possible pathways of succession.…”
Section: Introductionmentioning
confidence: 99%